Penatalaksanaan Terapi Latihan Pada Kondisi Post Sectio Caesarea Di RS PKU Muhammadyah Yogyakarta - Eka Putri, Ditha, Wahyuni SST.,FT.,M.Kes (2015)
Background: Sectio caesarea is a way of delivery of a fetus by making an incision in the wall of the uterus and teh wall ofthe abdominal. At the present time sectio caesarea much safer than the first with antibiotics, blood transfusions, surgery techniques are more perfect and anestesiyang better, because it occurs tend to do sectio caesarea without a sound basis, in this connection to keep in mind that a person who has undergone surgery sectio caesarea definitely uterine scar and each subsequent pregnancy and childbirth require careful monitoring of uterine rupture associated with danger (Wiknjosastro, 2005). Purpose: Scientific Paper aims to find out whether exercise therapy can reduce pain around the incision, preventing deep vein thrombosis, increase muscle strength abdominal and pelvic floor as well as improve patient funsional activity. Results: After treatment physiotherapy 6 times in patients with postoperative sectio caesarea obtained the following results silent pain reduction, from T1: mild pain, into T6: very mild pain, and tenderness of T1: severe pain, into T6: no pain so heavy, and painful motion of T1: pain severe enough, into T6: mild pain, increased strength of the flexor muscles of the pelvic floor T1: 2 to T6: 3: rotation of the trunk of T1: 2 to T6: 3: and increase in the functional activity of T1 : G (Depending 6 functions) into T6: A (Independent to 6 functions). Conclusion: Therapeutic exercise can reduce pain, prevent deep vein thrombosis, increasing the strength of the pelvic floor and improve functional activity.